The Quality Life of Children with Attention / Hyperactivity Disorder (ADHD) in Type C Special Schools in Bandung Indonesia - Mulya, Adelse Prima; Yani, Desy Indra; Ropi, Helwiyah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Attention Deficit Hyperactivity Disorder (ADHD) is a behavioral disorder characterized by attention deficit disorder, impulsive behavior, accompanied by excessive activity that is not in accordance with his age in childhood. ADHD can affect the quality of life of children. This study aims to describe the quality of life of ADHD children in SLB type C, Bandung. The design of this study is descriptive. The research subjects were 63 families who had ADHD children with an age range of 8-12 years who attended school in 5 types C SLB Bandung. Sampling using the total sampling technique with an inventory questionnaire, namely the QoL (PedsQL) questionnaire. Data analysis using descriptive analytics. The results showed that more than half of the quality of life of ADHD children was classified as poor. The quality of life of children with ADHD is very important because it contains various aspects of their lives, both from their physical, emotional, social, and school activities. This research clarifies quantifying the quality of life of ADHD children starting from physical, emotional, social and school functions. From these explanations, it is expected that in the part of the quality of life for ADHD children to experience deficiencies, and which parts can be improved and care and attention need to be improved.ABSTRAKGangguan Pemusatan Perhatian/Hiperaktivitas (GPPH) merupakan gangguan perilaku yang ditandai gangguan pemusatan perhatian, perilaku impulsif, disertai aktivitas berlebihan yang tidak sesuai dengan umurnya pada masa kanak-kanak. GPPH dapat berdampak terhadap penurunan kualitas hidup anak. Penelitian ini bertujuan untuk menggambarkan kualitas hidup anak GPPH di SLB tipe C Kota Bandung. Desain penelitian ini Deskriptif. Subjek penelitian 63 keluarga yang memiliki anak GPPH dengan rentang usia 8-12 tahun yang bersekolah di 5 buah SLB tipe C Kota Bandung. Pengambilan sampel menggunakan teknik total sampling dengan kuesioner inventory yaitu kuesioner kualitas hidup anak (PedsQL). Analisa data menggunakan deskriptif analitik. Hasil penelitian menunjukkan lebih dari separoh kualitas hidup anak GPPH tergolong kurang baik. Kualitas hidup anak dengan GPPH sangat penting, karena memuat berbagai aspek dalam kehidupannya baik dari kesehatan fisik, emosional, sosial, serta kegiatan disekolahnya. Penelitian ini memperjelas secara kuantitif kualitas hidup anak GPPH mulai dari fungsi fisik, emosi, sosial dan sekolah. Dari penjelasan tersebut, diharapkan pada bagian mana kualitas hidup anak GPPH mengalami kekurangan, serta dapat diperbaiki bagian mana yang kurang dan perlu ditingkatkan perawatan dan perhatiannya.